Efficacy of Subthreshold Micropulse Laser for Central Serous Chorioretinopathy - Fasler, Katrin; Turgut, Ferhat; Gunzinger, Jeanne Martine; Sommer, Chiara; Muth, Daniel Rudolf; Kinzl, Stephan; Nilius, Henning; Zweifel, Sandrine; Somfai, Gabor Mark (Klinische Monatsblätter für Augenheilkunde, 2024)
Purpose To evaluate the efficacy of a subthreshold micropulse laser (SML) in patients with central serous chorioretinopathy (CSCR).Methods Retrospective clinical study conducted at the Departments of Ophthalmology at a university and a municipal hospital in Zurich, Switzerland. We enrolled acute and chronic CSCR patients with persistent subretinal fluid (SRF) treated with SML. Two treatment protocols (fluorescein/indocyanine green angiography or optical coherence tomography guided) were evaluated for efficacy after 3 and 6 months. The primary outcomes of the study were reduction and percentage of eyes with complete resolution of SRF 3 and 6 months after SML treatment. Secondary endpoints included changes in central subfield thickness (CST) and visual acuity (VA) after 3 and 6 months.Results The study involved 37 eyes (35 patients, 48.6% chronic). A statistically significant reduction in SRF height and CST could be shown, irrespective of SRF duration, type of CSCR, or chosen guidance after 3 and 6 months: SRF − 40 µm (p < 0.01), CST − 52 µm (p < 0.01). Percentage of eyes with complete resolution of fluid at 3 and 6 months after SML were 24.3 and 21.6%, respectively. No statistically significant functional improvement (VA) could be shown. Multivariable regression and linear mixed regression analyses did not identify statistically significant differences in SRF reduction, CMT change, or VA improvement with respect to the type of CSCR or the treatment plan used (p > 0.05).Conclusion The effectiveness of SML in CSCR is under continuous debate. Our study findings demonstrate structural but only little functional changes with SML. In view of the shortage of verteporfin for photodynamic therapy, SML remains an important therapeutic option for CSCR patients.
Keywords: central serous chorioretinopathy; subthreshold micropulse laser; photodynamic therapy